The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/pr8080991
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wettability and Flow Rate on Oil Displacement Using Polymer-Coated Silica Nanoparticles: A Microfluidic Study

Abstract: Polymer-coated silica nanoparticles (PSiNPs) have been experimentally investigated in core- and micro-scale studies for enhanced oil recovery (EOR). Wettability and flow rate have a considerable effect on oil displacement in porous media. This work investigates the efficiency of PSiNPs for oil recovery on micro-scale at three wettability states (water-wet, intermediate-wet, and oil-wet). In addition, a cluster mobilization regime is considered in all experiments. A microfluidic approach was utilized to perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Surfasil has a short chain, consisting of dichlorooctamethyltetrasiloxane; when it is applied to a glass surface, the unhydrolyzed chlorines present on the chain react with silanol groups on the glass surface, forming a neutral or hydrophobic surface, depending on the concentration, film over the entire surface [17] . SurfaSil was diluted in heptane at a concentration of 1v/v % and 0.05v/v % to change the wettability towards oil-wet and intermediate-wet states, respectively [15] .…”
Section: Contact Angle Measurementmentioning
confidence: 99%
“…Surfasil has a short chain, consisting of dichlorooctamethyltetrasiloxane; when it is applied to a glass surface, the unhydrolyzed chlorines present on the chain react with silanol groups on the glass surface, forming a neutral or hydrophobic surface, depending on the concentration, film over the entire surface [17] . SurfaSil was diluted in heptane at a concentration of 1v/v % and 0.05v/v % to change the wettability towards oil-wet and intermediate-wet states, respectively [15] .…”
Section: Contact Angle Measurementmentioning
confidence: 99%
“…In the early 20th century, Wenzel et al [9] and Cassie et al [10] discovered that different surface roughness values would lead to different wettability of materials. Numerous studies have been conducted to explore the influence of wettability on biological attachments [11,12]. Since then, scholars from various countries have begun to design anti-fouling surfaces with different microstructures and have conducted a large number of experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…Schumacher et al [13] studied four types of microstructural surfaces with 2-mm spacing and 3-mm height. Patterns designed included geometric features of 2-mm-wide ribs of various lengths (4,8,12, and 16 mm), 2-mm-diameter circular pillars, 2-mm-wide continuous ridges, and 10-mm equilateral triangles. Experimental results showed that these surfaces correspondingly reduced spore settlement by 77%, 58%, 36%, and 31%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The functionalization or coating of the surface layer of the particle with polymer chains or other surface additive materials is a novel active area of scientific research; the technique has been desired for improving dispersion stability, for the stabilization of emulsions, to decrease the trapping or retention of NPs in porous media, and to improve the transport of NPs through reservoir pore channels, fundamental pre-requisites for nanoparticle oil recovery process. Omran et al [12] studied the potential of polymer-coated silica NPs to improve sweep efficiency on a micro-scale. Their study showed that NPs performed more efficiently in water-wet glass micromodels than in intermediate and oil-wet rock models.…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed that NPs performed more efficiently in water-wet glass micromodels than in intermediate and oil-wet rock models. The displacement efficiency was attributed to the ability of NPs to promote better clusterization of oil, thus leaving small and less connected oil drops trapped in the pores of the micromodel [12]. Saigal et al [13] reported that silica NPs covalently grafted with polymer chains (2-(dimethylamino)ethyl methacrylate) were extremely efficient emulsifier agents at low concentrations.…”
Section: Introductionmentioning
confidence: 99%